Increasing diversity on public and private sector boards - Part 2 What is being done to improve diversity on boards and how effective is this? - Sealy, Ruth; Doldor, Elena; Vinnicombe, Susan (Cranfield University, 2009)
The project was commissioned by the Government Equalities Office in order to examine the issue of diversity on boards of directors in the private and public sectors.The project addresses two main questions: Why are there so few women and other under-represented groups on public and private sector boards? and What is being done in order to increase diversity on boards? The report is published in two parts: Part I considered the available evidence on diversity on boards. It examined academic and non-academic literature in the field, in the UK and internationally, and reviewed available evidence concerning the factors accounting for the absence of diversity on boards.This second part maps out current practices aimed at increasing board diversity. It is based on interviews with several international experts in the field, giving case studies of various initiatives in four country contexts (UK, Norway, Spain and the Netherlands). In drawing together the report’s conclusion, some recommendations are formulated for further action to increase board diversity in the U
Keywords: Diversity, women on boards